A cradle-to-gate life cycle assessment of polyamide-starch biocomposites: carbon footprint as an indicator of sustainability - Äkräs, Laura; Silvenius, Frans; Baniasadi, Hossein; Vahvaselkä, Marjatta; Ilvesniemi, Hannu; Seppälä, Jukka (Springer Nature, 2024)
Accelerating climate change poses an alarming global issue, demanding a range of prompt and effective solutions. In response, bio-based plastics and biocomposites have emerged as extensively researched alternatives to combat the environmental threats posed by a warming climate. In this context, the present paper presents a cradle-to-gate life cycle assessment of a newly developed polyamide-starch biocomposite, with varying content of potato starch as the biofiller (ranging from 0 to 70 wt%). The primary aim was to quantitatively measure the total carbon footprint of the selected biocomposite. The results indicated that the progressive addition of potato starch as the biofiller into the copolyamide matrix significantly reduced the total carbon footprint of the biocomposite, achieving a maximum reduction of 42–43% with the highest starch content of 70 wt%. Moreover, the newly developed polyamide-starch biocomposite demonstrated excellent performance compared to reference fossil-based polyamides of polyamide 6 (PA6), polyamide 12 (PA12), and polyamide 6.6 (PA6.6), as well as composites of PA610/80 wt% polylactic acid modified by reactive extrusion (REX-PLA) and PA40/30 wt% glass fibers, with carbon footprint reductions of 29, 39, 42, 59, and 79%, respectively. Based on these findings, the polyamide-starch biocomposite, especially with the highest content of potato starch (70 wt%), exhibits significant potential as a new material solution to reduce the carbon footprint of several existing fossil- and bio-based polyamides together with polyamide-based composites. In doing so, it contributes to advancing the development of a more climate-friendly future for plastics through reductions in their carbon footprints.
Keywords: copolyamide; starch; biocomposite; life cycle assessment (LCA); · cradle-to-gate approach; carbon footprint